The Academics of Standard Setting: A Field Study of Financial Reporting Standard Setters’ Engagement with Academic Research - Garavaglia, Shannon; Hayne, Christie; Mongold, Cassie (The Accounting Review, 2026)
ABSTRACT Financial reporting standard-setting bodies are expected to include academic research in their decision-making processes. However, little is known about whether, why, and how they engage with research. We interview staff from two major accounting standard-setting bodies and, using the information seeking and communication model as a theoretical lens, identify factors shaping their research engagement. These factors include perceptions of academic research, search difficulties, and challenges with assessing the credibility and utility of academic research. Our findings reveal an unstructured, idiosyncratic approach to information seeking, a reliance on academic papers over direct researcher interaction, a significant lack of two-way communication, and concerns relating to incentive differences between academics and standard setters. These structural issues limit the extent to which academic research can inform standard setting. We provide insights on improving the inclusion of academic research in the standard-setting decision-making process and contribute to broader discussions on research relevance. JEL Classifications: M41; M48.